Barthesian semiotics in Jungkook's “SOMEBODY”: Love and Heartbreak - Putri, Aulia; Putri, Dian Widya (CAHAYA PENDIDIKAN, 2025)
Music is a strong medium that touches feelings, strengthens cultural narratives, and also challenges the myths of society. This study adopts Roland Barthes' semiotic theory analyzing song “Somebody” by Jungkook, focusing on between denotation, connotation, and myth. Using qualitative content analysis, the study investigates how it constructs and deconstructs romantic myths about love, heartbreak, and emotional detachment. While the lyrics do follow traditional narratives-eternal love and moving on linearly-eventually its betray those ideals by illustrating heartbreak as rather complex and non-linear. The revelation this study provides is that “Somebody” operates both as reflecting dominant ideological configurations in the culture and a criticism of them, thereby, adding even more nuanced reflections on post-breakup emotions. Engaging Barthesian semiotics, this study brings to light the popular music's view of creating and recreating perceptions of love, loss, and resilience the listener might have. The findings are also part of broader debates on semiotics in music beyond the narrative of contemporary culture as relevant to the lyrical narrative.